Experimental Investigation on the Bonding Strength between Coating and Matrix in Arc Spraying 3cr13 - Hou, Yali; Li, Changhe; Wang, Sheng; Zhao, Tingting (Recent Patents on Materials Science, 2014)
A large number of patents have been recently devoted to the development of rapid molding technology using metal arc spraying with high-melting-point and high-hardness metals (carbon and alloy steels). Manufacturing arcspraying dye is attractive because not only is the material relatively cheap but the dye shell also has properties of high hardness and high strength that greatly improves the service life of the spraying dye. The application scope of the spraying dye is thus expanded to provide better forming precision for the manufacture industry. Among these patents is a highmelting- point metal mold shell non-internal stress rapid manufacturing process and device. This patented technology involves the use of a high-melting-point metal wire material as self-fluxing electrode and arc, and extremely high temperature generated by gas discharge is used as a heat source. The high-melting-point metal material is atomized in a molten state under high-speed gas flow of compressed gas, and the molten particles are sprayed and deposited on the alloyed master mold (matrix) surface. In this paper, the bonding strength between coating and matrix in arc spraying 3cr13 was experimentally investigated. The coating formation principle and the bonding method between the coating and the matrix were analyzed. Furthermore, the effects of spraying distance, matrix preheating temperature, and matrix surface roughness on bond strength were discussed. The experimental results showed that the bond strength between coating and matrix initially increased and subsequently decreased with increasing spray distance. The maximum bond strength was 15.8MPa at a spraying distance of 200mm. Higher particle speed results in higher particle flatness rate and higher bond area between particle and matrix. Moreover, matrix preheating temperature also has a significant effect on bond strength; bond strength gradually increased along with increasing temperature. The bond strength between coating and matrix initially increased and then decreased with increasing surface roughness (Rz). When Rz was near 0.5mm, the bond strength between coating and matrix reached the maximum value.
Keywords: molten drop